Penguindrum. 1 - Ikunichawder; Gray, Lora (Seven Seas Entertainment, 2019)
As twin brothers Kanba and Shoma search for a powerful artifact to repay a mysterious entity who saved the life of their terminally ill little sister Himari, they must compete with several rivals who also seek the elusive treasure.